Study of association and diagnostic utility of novel anthropometric and lipid indices for nonalcoholic fatty liver disease: A hospital-based study - Anand K. Pyati; Sakthivadivel Varatharajan; Abhishek Arora; Vaman Kulkarni; Aparna Varma Bhongir; Sangeetha Sampath; Gomathi Ramaswamy; Madhu Latha Karra; Priyanka Das; Pawan Pagaku (Journal of Family Medicine and Primary Care)
Context: Given the prevalence of nonalcoholic fatty liver disease (NAFLD) of 25% and an expected prevalence of 55.4% by 2040 and its associated complications, it is essential to prioritize large-scale screening programs in the general population. Objectives: 1. To examine the association of the conventional and novel anthropometric and lipid indices in NAFLD and 2. To determine diagnostic ability, their cutoff values, and best parameter/model for detecting NAFLD. Settings and Design: A case-control study was done among 262 NAFLD cases and 186 non-NAFLD controls in a tertiary care hospital. Methods and Material: BMI, WC/Ht, LAP, VAI, TC, TG, HDL, LDL, VLDL, Non-HDL-C, TG:HDL-C, TC:HDL-C, LDL-C/HDL-C, TyG, CMI, RC, AIP, and AC were measured/calculated by recommended methods. Statistical Analysis Used: Binary univariate and multivariate logistic regression analyses and ROC analysis to determine the association, best statistical model, and diagnostic validity of study variables. Results: The individuals with BMI >30 had highest risk (OR = 9.636) of NAFLD followed by those with TG >500 mg/dl (7.054), LAPM (3.157) and LAPF (2.975), WC (M) (3.07), WC:Ht >0.6 (2.893), TyG (2.361), VAI-M (2.053), and VAI-F (2.253) in decreasing order. On ROC analysis, anthropometric parameters outperformed the lipid indices, among which BMI [AUC = 0.702; P < 0.001] and WC [0.671; P < 0.001] showed the highest AUC, followed by WC:Ht [0.657; P < 0.001]. Among lipid indices, LAP had the highest AUC [0.666; P < 0.001], followed by CMI [0.629; P < 0.001] and TyG [0.621; P < 0.001]. Conclusion: BMI, WC, LAP, WC/Ht, VAI, CMI, and TyG are the best simple and reliable indices for predicting/detecting NAFLD in the decreasing order of their diagnostic abilities which can identify the population at risk of NAFLD.